International Dock Work Conventions in the era of post-globalization - Jason Angelopoulos; Constantine Chlomoudis; Eustratia Dalvadani (SPOUDAI - Journal of Economics and Business, 2014)
The part of the port industry that serves international trade flows, competes and satisfies demand with global characteristics. Port services production and supply, within an open market, can only be governed by global regulations, and should be taken into account by those who wish to implement them. International organizations influence both safety aspects and the protection of professional life from new working methods in ports. Assessing the importance of labor factor in ports, it is argued that it constitutes a key factor in port production. Several factors have facilitated the gradual substitution of port manual labor, leading to changes in both requirement in skilled labor quantity, but also labor skill and quality requirements. Studying the three I.L.O. conventions pertaining to dock work (C032, C137 and C152) we argue that they can form a positive model for the integration of work rules on a global scale. Main aim of these conventions is the mutual development for all port stakeholders and prevention of unfair competition. We assess the current state of acceptance and degree of implementation of the Conventions by national governments, and argue for the mutual benefits for port stakeholders arising from their implementation, from the perspective of globalization governance, in the era of post - globalization.
Keywords: R41; J28; M54; 330; ILO Conventions; Port labor; dock work; global regulations